Intimate partner violence reported by female and male users of healthcare units - Claudia Renata dos Santos Barros; Lilia Blima Schraiber
ABSTRACT OBJECTIVE To analyze nonfatal violence suffered and committed by adult men and women, in an intimate relationship. METHODS The participants in the research were women aged between 15 and 49 years and men between 18 and 60 years, interviewed by face-to-face questionnaire application. The sample selection was of consecutive type, according to the order of arrival of the users. We conducted temporarily independent investigations and covered different health services to avoid couples and relationships in which the retaliation could be overvalued. To improve the comparison, we also examined reports of men and women from the same service, i.e., a service that was common to both investigations. We compared the situations suffered by women according to their reports and cross-linked the information to what men, according to their own reports, do against intimate partners or ex-partners. We also examined the cross-linked situation in reverse: the violence committed by women against their partners, according to their reports, in comparison with the violence suffered by men, also according to their reports, even if, in this case, the exam refers only to physical violence. The variables were described using mean, standard deviation, frequencies and proportions, and the hypothesis testing used was: Fisher's exact and Pearson's Chi-square tests, adopting a significance level of 5%. RESULTS Victimization was greater among women, regardless of the type of violence, when perpetrated by intimate partner. The perception of violence was low in both genders; however, women reported more episodes of multiple recurrences of any violence and sexual abuse suffered than men acknowledged to have perpetrated. CONCLUSIONS The study in its entirety shows significant gender differences, whether about the prevalence of violence, whether about the perception of these situations.